Impact of climate and land use change on the erosion of the upstream Kelara Watershed. Issue 2 (July 2021) - Limbong, A; Barkey, R; Umar, A; Rijal, S; Nursaputra, M; Chairil, A
Abstract: South Sulawesi has been affected in recent years by natural disasters. One of the areas affected by the flood disaster is the Jeneponto District, which is included in the Kelara Watershed ecosystem's boundary. Extreme weather conditions cause flood disasters, and land use in the upper reaches of the Kelara watershed do not match its designation, which causes an increase in the rate of erosion. Climate change analysis with projected precipitation from the CSIRO General Circulation Model Mk3.5. The estimated land cover change uses a combination of the Geographic Information System, remote sensing, and Markov Chain Cellular Automata method with Landsat images. Prediction of erosion rates using the Universal Soil Loss Equation method. The annual rainfall of 2026 has decreased due to a significant decrease in rainfall during the dry season. In 2006-2016, changes in land use were not significant. In the land-use projection for 2026, there will be significant changes in land use. The use of paddy fields has increased over a wider area, while other land uses continue to follow the previous trend of reducing the surface. The prediction of future erosion will only increase by one ton/ha/year. Intense erosion classes will experience a reduction in the area of about 200 hectares in 2026. Based on this, the land is not a problem in the future, but an issue that must be prepared for its management is a drought when considering climate change conditions.